PERENCANAAN MASTERPLAN EMBUNG WISATA DESA KUNYIT KECAMATAN BAJUIN KABUPATEN TANAH LAUT - Anton Kuswoyo; Budi Kurniawan Budi; Mufrida Zein; Marlia Adriana; Siti Fitriati (Pusat Penelitian dan Pengabdian Kepada Kepada Masyarakat Politeknik Negeri Tanah Laut, 2022)
Kunyit Village, Bajuin District, Tanah Laut Regency, South Kalimantan, has the potential to become a tourist village. This is because Kunyit Village is topographically and geographically very supportive to be developed into a tourist village. Kunyit Village Tourism Reservoir is designed to be the only Reservoir in Tanah Laut Regency even in South Kalimantan which has complete facilities for visiting. It is necessary to make an initial stage in the form of planning masterplan to become a guide for the development of the Kunyit Village Tourism Reservoir for the next five years. The method used is a qualitative technique, which is used in identifying the characteristics of tourist objects and formulating a concept. Data collection techniques using primary surveys and secondary surveys. The results of the discussion are regional conditions, existing tourism conditions in the form of SWOT analysis, potential analysis (economic, social, cultural, environmental, educational), and planning analysis masterplan in the form of planning for 16 building facilities at the Kunyit Village Tourism Reservoir.